The Formation of Perfect, Imperfect, Imperative, of Indonesian and Arabic Verbs: A Contrastive Analysis - Ansori Ansori; Fahrurrazi Fahrurrazi (Kawanua International Journal of Multicultural Studies, 2022)
Arabic and Indonesian have different constructions in the formation of the verb tenses. The purpose of this study is to describe the process of formation of tense verbs in Arabic and Indonesian, to analyze the differences in the formation of tenses between the two languages. The method used in this research is qualitative with contrastive analysis. The results of this study describe the formation of Arabic tense verbs through internal modification and affixation, while the formation of Indonesian verbs is realized lexically. The difference between the two is that the formation of verbs in Arabic is always related to time, quantity, and gender differences, are expressed grammatically through verbs changes, while the formation of verbs in Indonesian is not related to time, and gender thus expressing the semantic concepts of time, quantity, and gender are lexically represented by accompanying verbs to form verb phrases without changing their verb forms.